Manual de seguridad industrial y salud ocupacional según la norma técnica OHSAS 18001 para la compañía Jatarig del cantón Quevedo, año 2014 - Cedeño Cuesta, Jonh Fernando (2015)
This research work, aimed to make the Handbook of Industrial safety and occupational health according to the OHSAS 18001 standard technique for company "JATARIG", of the canton Quevedo. This research using survey method determined in a first target that the company JATARIG not had a system of industrial safety and that deficiency in security was very high, putting at risk the health of its workers and on the basis of this information was the risk map of the company which were determined the risks to which the workers of the company the majority of mechanical nature In addition to the areas of greatest danger (criticism) in which it must intervene to empowering workers to prevent accidents, the third objective was accomplished in establishing rules and procedures based on the technical standard OHSAS 18001 from different jobs and use of protective equipment within the company that specifies the secure way to work as well as the correct use of the EPP. The previous point served as the basis to define the safety manual from the company which lists all the policies of the company in relation to: safety and hygiene, alcohol - tobacco, transport, disciplinary, entering the company formation, the operation of the safety Committee of the company, in the event of accidents, the use of personal protective equipment use of hand tools, the use of electrical machines, the use of a lathe, welding operations and procedures according to each of the machines and actions within the company. Based on the above was true the hypothesis of industrial safety and occupational health in Enterprise JATARIG manual will greatly reduce the risks present in the same.